Ambulatory Melanoma Care Patterns in the United States. (21st August 2013) - Ji, Andrew L.; Baze, Michael R.; Davis, Scott A.; Feldman, Steven R.; Fleischer, Alan B.
Abstract : Objective . To examine trends in melanoma visits in the ambulatory care setting. Methods . Data from the National Ambulatory Medical Care Survey (NAMCS) from 1979 to 2010 were used to analyze melanoma visit characteristics including number of visits, age and gender of patients, and physician specialty. These data were compared to US Census population estimates during the same time period. Results . The overall rate of melanoma visits increased (P < 0.0001 ) at an apparently higher rate than the increase in population over this time. The age of patients with melanoma visits increased at approximately double the rate (0.47 year per interval year, P < 0.0001 ) of the population increase in age (0.23 year per interval year). There was a nonsignificant ( P = 0.19 ) decline in the proportion of female patients seen over the study interval. Lastly, ambulatory care has shifted towards dermatologists and other specialties managing melanoma patients and away from family/internal medicine physicians and general/plastic surgeons. Conclusions . The number and age of melanoma visits has increased over time with respect to the overall population, mirroring the increase in melanoma incidence over the past three decades. These trends highlight the need for further studies regarding melanoma management efficiency.